POWERFUL ACTOR IDENTIFICATION IN COMMUNITY FORESTRY VIA ACTOR-CENTERED POWER THEORY: CASE STUDY IN SON LA PROVINCE - Duy Bach, Ngo (Journal of Forestry Science and Technology, 2018)
Community forestry is known as a new trend of forest management in which forest management role is entrusted to local communities at local levels. However, it is de factor observed that there exists a relationship between the context of political processes and the dynamics of social interactions amongst the actors. Communities are vulnerable to the influence of powerful relevant actors. Across all cases in the research site, 13 relevant actors involving in community forestry activities are identified. Applying "Actor-Centered Power" theory allows us to do quantitative calculation of power element of the relevant actors (Coercion, Incentive/disincentive, and Dominant information). Calculation results explain that how powerful relevant actors build their power based on power elements. Especially, research results pointed out that political actors still are the most powerful actors steering community forestry process in all cases. This means state agencies still dominate in forest management in general and community forestry process in particular.